Hubungan Kadar P-selectin dengan Fungsi Atrium Kiri pada Stenosis Mitral Rematik - Prafithrie Avialita Shanti; Yoga Yuniadi; Nur Haryono (Jurnal Kardiologi Indonesia, 2014)
Background. Mitral stenosis (MS) prevalence remains significant in developing countries because of the prevalence of Rheumatic Heart Disease (RHD). In moderate-severe MS patients, enormous increase in turbulent region and shear stress cause vascular endothelial dysfunction, and as the consequence, it increases the risk of thromboembolic complications. P-selectin is an adhesion molecule that play a role in the inflammation process, where it is expressed rapidly in mere minutes. Left Atrial Volume Index (LAVI) is a superior parameter compared with other two-dimensional echocardiography method to assess left atrial function.Methods. This was a cross-sectional study involving 20 MS moderate-severe patients with mitral valve area (MVA) < 1.5 cm2, to whom successful Percutaneous transvenous Balloon Mitral Valvulotomy (PBMV) was performed. Samples were taken consecutively from May-October 2013 at the National Cardiovascular Center Harapan Kita, Jakarta. Blood samples of P-selectin were collected pre and post-PBMV. The result was statistically analyzed with echocardiography data of LAVI prior PBMV to describe any association between expression of P-selectin and atrial function.Result.We found no association between LAVI and P-selectin level pre and post-PBMV in MS patients. That is described in the value of pre PBMV ?=-0.103 (95% CI -0.251-0.045) with p=0.16 and post-PBMV ?= 0.009 (95% CI -0.155-0.172) with p=0.91 We then performed linear regression test with adjusted confounding variable including sex, age, and atrial fibrillation, still we found no association between LAVI and P-selectin level, with the value of pre PBMV ?= -0.154 (95% CI -0.340-0.032) p=0.09 and post PBMV ?= -0.049 (95% CI -0.250-0.152) p=0.61.Conclusion. There is no difference in P-selectin level pre and post PBMV. There is no association between poor LAVI value and expression of P-selectin pre and post PBMV in MS.